PENGARUH FIRM SIZE, LEVERAGE, NET WORKING CAPITAL, GROWTH OPPORTUNITY TERHADAP CASH HOLDING - Yacub, Shannen Evelyn; Widyasari, Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research was conducted with the aim of obtaining empirical evidence regarding the effect of firm size, leverage, net working capital, growth opportunities on cash holdings. This study uses secondary data obtained from the financial reports of property and real estate companies through the website www.idx.co.id.. The population in this study is all property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2021 . This research was conducted by taking 27 samples of companies that match the predetermined criteria and using multiple linear analysis tests with purposive sampling technique with quantitative methods. The results of the partial test (t test) show that firm size and leverage have a significant effect on cash holdings, while net working capital and growth opportunities have no significant effect on cash holdings. The implication of this research is the need for appropriate company policies for managing cash on hold, in order to earn profits effectively.